How to use prescriptive analytics for sales reports - Ross, Joris (My University, 2019)
Organizations are becoming more and more data-driven nowadays, a lot of data is gath-ered to be analyzed within these organizations. However, not all of the data that is gathered by these organizations will be analyzed. The problem that arises in this scenario is that data is being gathered unnecessarily. One of the departments within organizations that has to deal with this problem is the sales department. Their special status within organizations, together with their different ‘culture’ within organizations makes it so that it is not seen necessary for them to be-come more efficient with the use of data-driven decision-making. Based on the qualitative research done in this thesis, it was concluded that to improve the sales reports for the sales departments, the use of prescriptive analytics tools could be the solution. When applied correctly, these tools can help to increase the efficiency of the sales reports, as well as a more data-driven decision-making for your organization.
Keywords: Business Intelligence, prescriptive analytics, sales reports